Book Review of Feminism and Ruralities - Herman Cuervo (Journal of Research in Rural Education, 2016)
In their new edited book, Feminisms and Ruralities, Barbara Pini, Berit Brandth, and Jo Little bring together a collection of essays that discuss the intersection of feminism and rural studies. The plural in the title of their edited volume reveals their concerns and aims: to bring into conversation the multiplicity of feminisms and ruralities that intersect with and impact rural everyday lives. That is, a driving force in their book is to highlight the diff erent ontological manifestations of feminism and rurality; how and why they intersect; what can they tell us about the profound social, economic, and cultural structural changes in rural life; and how they challenge traditional assumptions of rural identities. The result is an important book that illustrates the complexity and contested nature of both concepts, and that highlights the theoretical and empirical work that has been done and needs to follow in order to fi ll the research gap around the concept of diff erence in rural spaces.